Pembelajaran Akidah Akhlak Berbasis Moodle - Yusfar Ramadhan; Fia Khuzainatul Makkiyah (Universitas Al-Amien Prenduan, 2022)
The e-learning platform is a solution for schools during the ban on face-to-face learning due to the Covid-19 virus. This study aims to analyze the process of planning, implementing and assessing online learning using the Moodle application on the subject of Akidah Akhlak, the main subject Syirik . This study used a qualitative approach to classroom research. The subjects of this study are the principal, the teacher of Akidah Akhlak and students of class X IPS in MA Annur Alhuda Tajinan Malang. The data collection technique used purposive random sampling. Collecting data used observation, interview and documentation techniques. Data analysis used data triangulation technique. The results of this study indicate that the planning are (1) implementing a simulation, (2) determining the technical implementation, (3) an online learning schedule, and (4) planning the curriculum, syllabus and lesson plans, while the implementation is through 7 features, namely attendance, subject matter, material files, chats, discussion forums, daily assignments and feedback, while the assessment is taken from 3 features, namely (1) attendance, (2) discussion forums, (3) daily assignments / quizzes. The online learning based Moodle works well and highly effective in helping distance learning.